2013
DOI: 10.1161/strokeaha.113.000883
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke or Systemic Embolism in Atrial Fibrillation Patients Treated With Warfarin

Abstract: Background and Purpose-Although oral anticoagulants (OACs) are highly effective in reducing stroke risk in atrial fibrillation, some patients still sustain stroke despite being on an OAC. Our aim was to identify the risk factors that contribute to stroke risk in atrial fibrillation, although patients were taking OACs in a clinical trial setting. Methods-We identified contemporary clinical trials that investigated OACs in patients with atrial fibrillation. Event rates per year from each study and pooled event r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 41 publications
3
66
0
5
Order By: Relevance
“…A meta-analysis of 6 randomized clinical trials (SPORTIF III and V, BAFTA, RE-LY, ROCKET-AF, and ARISTOTLE) concluded that older age, female gender, previous stroke/TIA, vitamin K-antagonist naïve status, renal impairment, previous aspirin use, and higher CHADS2 score were associated with a higher relative risk of stroke on oral antithrombotic therapy. 17) In this study, we measured the echocardiographic parameters associated with warfarin-resistant LA thrombus in addition to clinical characteristics, because LA thrombus is a definite cause of stroke. Among the 431 NVAF patients administered warfarin, 10 (2.3%) had an LA thrombus even when taking a therapeutic dose for ≥ 1 months.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 6 randomized clinical trials (SPORTIF III and V, BAFTA, RE-LY, ROCKET-AF, and ARISTOTLE) concluded that older age, female gender, previous stroke/TIA, vitamin K-antagonist naïve status, renal impairment, previous aspirin use, and higher CHADS2 score were associated with a higher relative risk of stroke on oral antithrombotic therapy. 17) In this study, we measured the echocardiographic parameters associated with warfarin-resistant LA thrombus in addition to clinical characteristics, because LA thrombus is a definite cause of stroke. Among the 431 NVAF patients administered warfarin, 10 (2.3%) had an LA thrombus even when taking a therapeutic dose for ≥ 1 months.…”
Section: Discussionmentioning
confidence: 99%
“…W dużych bazach danych występowanie CKD wiąże się z udarami i krwawieniami [410,411]. Leczenie przeciwzakrzepowe można bezpiecznie stosować u pacjentów z umiarkowaną i umiarkowanie ciężką CKD ([współczynnik przesączania kłębuszkowego (GFR) ≥ 15 ml/min]: CKD w 3. stadium (oszacowany GFR < 59 ml/min/1,73 m 2 ) występowała u 805 spośród 1936 pacjentów objętych randomizacją w badaniu Stroke Prevention in Atrial Fibrillation (SPAF) i w tej grupie uzyskano dobre efekty leczenia warfaryną (INR 2-3) [412].…”
Section: Doustne Leczenie Przeciwzakrzepowe U Pacjentów Z Migotaniem unclassified
“…Больные высокого риска, имею-щие ≥ 4 баллов по шкале CHA 2 DS 2 -VASc, имели наихудший прогноз по сравнению с другими больными, что согласуется с данными иссле-дований [6,8,16,22]. Ранее нами было показа-но [23], что количество баллов по шкале CHADS 2 ≥ 3 у больных с ФП явилось предикто-ром развития комбинированной конечной то-чки (ИИ/ТИА, сердечно-сосудистая смерть, острый коронарный синдром).…”
Section: Discussionunclassified